Pengembangan Sistem ERP untuk Distribusi Produk PT Solomon Indo Global: Modul Shipping, Inventory, dan User Management - Afif Ghani Zahran; Rizka Hadwiyanti; Agung Brastama Putra (STMIK Banjarbaru, 2025)
Digital transformation is driving companies to integrate technology to improve efficiency. PT Solomon Indo Global, a fast-moving consumer goods company, faces distribution challenges due to a lack of system integration, such as the absence of multi-warehouse stock records, undocumented distribution flows, and unclear partner roles. This study aims to develop an integrated Enterprise Resource Planning (ERP) system with a focus on the User Management, Inventory, and Shipment modules. The methodology employs a 5-Stage ERP Implementation approach (Project Preparation, Business Blueprint, Realization, Final Preparation, Go Live and Support) without a direct implementation phase. Problem identification was conducted through interviews and observations, followed by mapping of the as-is and to-be business processes, and system development using the Scrum method (backlog, sprint, daily Scrum, review, retrospective). The research results produced an integrated ERP system design that includes the main modules of user management, inventory, shipment, and sales support, which has proven to improve the efficiency of the company's distribution process.Keywords: Enterprise Resource Planning; Supply chain; Scrum Method; Logistic AbstrakTransformasi digital mendorong perusahaan mengintegrasikan teknologi guna meningkatkan efisiensi. PT Solomon Indo Global, sektor barang konsumsi cepat, menghadapi tantangan distribusi akibat kurangnya integrasi sistem, seperti tidak adanya pencatatan stok multi-gudang, alur distribusi tidak terdokumentasi, dan peran mitra yang belum jelas. Penelitian ini bertujuan mengembangkan sistem Enterprise Resource Planning (ERP) terintegrasi dengan fokus pada modul User Management, Inventory, dan Shipment. Metodologi menggunakan pendekatan 5 Stages ERP Implementation (Project Preparation, Business Blueprint, Realization, Final Preparation, Go Live and Support) tanpa tahap implementasi langsung. Identifikasi masalah dilakukan melalui wawancara dan observasi, dilanjutkan pemetaan proses bisnis as-is dan to-be, serta pengembangan sistem menggunakan metode scrum (backlog, sprint, daily scrum, review, retrospective). Hasil penelitian menghasilkan rancangan sistem ERP terintegrasi yang memuat modul utama user management, inventory, shipment, serta dukungan sales, yang terbukti mampu meningkatkan efisiensi alur distribusi perusahaan.Kata Kunci: Enterprise Resource Planning; Rantai pasok; Metode scrum; Logistic